Reinventing American Protestantism : Christianity in the new millennium - Miller, Donald E. (Donald Earl), 1946- (University of California Press, 1997)
Explores the trend in the last thirty years towards new paradigm churches, sometimes called megachurches or postdenominational churches, which are reinventing Christianity by redefining the institutional forms and reconnecting people to the message of first-century Christianity using the media of twentieth century America.
Keywords: Calvary Chapel (Costa Mesa, Calif.); Hope Chapel (Hermosa Beach, Calif.); Vineyard Christian Fellowship.; Vineyard Christian Fellowship; Protestant churches -- United States -- Forecasting.; Protestant churches -- California, Southern -- Case studies.; Pentecostal churches -- California, Southern -- Case studies.; California, Southern -- Religious life and customs.; United States -- Church history -- 20th century.; Calvary Chapel movement.; Églises protestantes -- États-Unis -- Prévision.; Églises protestantes -- Californie (Sud) -- Études de cas.; Églises pentecôtistes -- Californie (Sud) -- Études de cas.; Californie (Sud) -- Vie religieuse.; États-Unis -- Histoire religieuse -- 20e siècle.; RELIGION -- Christianity -- Protestant.; RELIGION / Christianity / General; Calvary Chapel movement; Pentecostal churches; Protestant churches; Protestant churches -- Forecasting; Southern California; United States; Protestantisme.; Verenigde Staten.; Christianity.; Religion.; Philosophy & Religion.; 1900-1999; New paradigm churches; Case studies; Church history; Prognoses (vorm)